Mass spectrometric fragmentation and photocatalytic transformation of nicotine and cotinine. (11th November 2016) - Medana, Claudio; Santoro, Valentina; Bello, Federica Dal; Sala, Cecilia; Pazzi, Marco; Sarro, Marco; Calza, Paola
Abstract : Rationale: Nicotine and cotinine are, respectively, alkaloids produced mainly by the Solanaceae plant family, especially tobacco, and its most important human metabolite. These compounds are frequently found as contaminants in wastewater or landfill samples and they could be used to evaluate pollution by tobacco use. The aim of this study is to improve the knowledge about possible transformation pathways of nicotine and cotinine. This would help the identification of degradants by using HPLC coupled with a high resolving power mass analyzer (LTQ‐Orbitrap). In addition, we evaluated toxicity on bioluminescent photobacteria to indicate possible relationships between the formation of transformation products and their toxic effects. Methods: The transformation of nicotine and cotinine and the formation of intermediate products were evaluated adopting titanium dioxide as photocatalyst. The structural identification of photocatalytic transformation products of these two alkaloids was based on LC/multistage MS experiments. High‐resolution MS allowed the elemental composition of these products to be hypothesized. The evolution of toxicity as a function of the irradiation time was also studied using a bioluminescent photobacterium ( Vibrio fischeri ) test. Results: Several products were formed and characterized using HPLC/HRMS n . The main photocatalytic pathways involving nicotine and cotinine appear to be hydroxylation, demethylation and oxidation. Nine degradants were formed from nicotine, including cotinine. Seven degradants were generated from cotinine. There is no transformation product in common between the two studied molecules. Conclusions: The study of photocatalytic degradation allowed us to partially simulate human metabolism and the environmental transformation of the bioactive alkaloid nicotine. We searched for some of the identified transformation products in river water and landfill percolate by solid‐phase extraction and HPLC/HRMS and eventually their presence was confirmed. These new findings could be of interest in further metabolism and environmental pollution studies. Copyright © 2016 John Wiley & Sons, Ltd.